Dangerous talk : scandalous, seditious, and treasonable speech in pre-modern England - Cressy, David (Oxford University Press, 2010)
Dangerous Talk examines the 'lewd, ungracious, detestable, opprobrious, and rebellious-sounding' speech of ordinary men and women who spoke scornfully of kings and queens. Eavesdropping on lost conversations, it reveals the expressions that got people into trouble, and follows the fate of some of the offenders. Introducing stories and characters previously unknown to history, David Cressy explores the contested zones where private words had public consequence. Though 'wordswere but wind', as the proverb had it, malicious tongues caused social damage, seditious words challenged political author.